2009
DOI: 10.1002/aic.11859
|View full text |Cite
|
Sign up to set email alerts
|

Effect of molecular weight of poly(N‐isopropyl acrylamide) temperature‐sensitive flocculants on dewatering

Abstract: (PNIPAM) (temperature-sensitive flocculant) on sedimentation rate, sediment density, and supernatant clarity of silica suspensions was investigated. The addition of PNI-PAM resulted in rapid sedimentation (T [ critical solution temperature, CST) and low sediment moisture (T \ CST). Higher MW polymers resulted in more effective flocculation and sediment consolidation. At 10 ppm, PNIPAM (3.6 million Da) produced 20 m/h settling rate and 48 vol % solids sediment density, whereas 0.23 million Da polymer produced 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 23 publications
4
54
1
Order By: Relevance
“…For this reason, the presence of PNIPAM on silica surfaces causes a small decrease in the magnitude of the negative zeta potential of the silica surfaces, with the magnitude of the zeta potential becoming smaller with increasing polymer molecular weight. This is consistent with adsorption studies performed by Li et al [15], which showed that the adsorption density of PNIPAM onto silica surfaces significantly increases with the increase in polymer molecular weight. The adsorption measurements have also shown that at temperatures below the LCST, PNIPAM does adsorb onto silica surfaces, but to a much lesser extent than at higher temperatures.…”
Section: Effect Of Pnipam On the Surface Charge Of Silica Surfacessupporting
confidence: 90%
See 2 more Smart Citations
“…For this reason, the presence of PNIPAM on silica surfaces causes a small decrease in the magnitude of the negative zeta potential of the silica surfaces, with the magnitude of the zeta potential becoming smaller with increasing polymer molecular weight. This is consistent with adsorption studies performed by Li et al [15], which showed that the adsorption density of PNIPAM onto silica surfaces significantly increases with the increase in polymer molecular weight. The adsorption measurements have also shown that at temperatures below the LCST, PNIPAM does adsorb onto silica surfaces, but to a much lesser extent than at higher temperatures.…”
Section: Effect Of Pnipam On the Surface Charge Of Silica Surfacessupporting
confidence: 90%
“…4). The repulsive force can instead be attributed to steric repulsion, resulting from a low level of adsorption of fully extended and hydrated PNIPAM molecules [14,15,28]. Contact angle measurements have shown that the presence of PNIPAM on silica surfaces slightly increases their hydrophobicity (see Fig.…”
Section: Pnipam-induced Hydrophobic Attraction and Adhesion Between Smentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to van der Waals attraction, it has been proposed that the poorly soluble polymeric stabilizers on the particle surface induce an additional 'hydrophobic' attraction. The 'hydrophobic' attraction was first 35 presented by Klein,38,39 who observed the presence of an attractive force in a poor organic solvent for two approaching polymeric coated surfaces. This observation was also seen recently by the Franks group 40 during their temperature investigation of the hydrophilic/hydrophobic nature of poly(N-40 isopropylacrylamide) (PNIPAM) in order to manipulate interparticle interactions.…”
mentioning
confidence: 97%
“…He used zircon suspension and methylcellulose as the thermosensitive agent. Identical conclusions were made in other papers Li et al, The aggregation via standard flocculation runs in four steps (Gregory, 1993). In the first step a polymer is added to the solution and they are mixed.…”
Section: Introductionmentioning
confidence: 95%